PENAMBAHAN SEPERTIGA HUKUMAN BAGI PELAKU TINDAK PIDANA PERDAGANGAN ORANG PERSPEKTIF HUKUM PIDANA ISLAM - Safitri, Vera Chatuningtias (Al-Jinayah: Jurnal Hukum Pidana Islam, 2016)
Abstract: This article highlights the 1/3 additional punishment to perpetrator of the trafficking crime. It is a criminal stipulation as mentioned in Criminal Code Article 7, paragraph (1) added to the 1/3 aggravated punishment, because it contains trafficking and heavy maltreatment (serious injury), severe mental disorder, infectious disease, other life-threatening, pregnancy, or impaired and a loss of reproductive function of the victim. The perpetrator of which is imprisoned for a minimum 4 years and maximum 20 years with the criminal fine of at least Rp. 160,000,000.00 and at most Rp. 800,000,000.00. While in fiqh jinayah, the 1/3 additional punishment included in the theory of âuqÃ»bah al-badaliyyah al-takmÃ®liyyah (substitute and complement punishment). Criminalization of âuqÃ»bÃ¢h al-badaliyyah al-takmÃ®Ã®liyyah is an additional punishment that follows the principal penalty after the issuance of the verdict of the judge. The penalties included in this jarimah are physical punishment and diyat kamilah.Keywords: Additional penalty, trafficking, Islamic Criminal Law.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Abstrak: Penambahan 1/3 hukuman bagi pelaku tindak pidana perdagangan orang adalah penetapan pidana dalam KUHP Pasal 7 ayat (1) ditambahkan dengan diperberat 1/3 hukuman, karena mengandung unsur trafficking dan ditambah melakukan penganiayaan berat, gangguan jiwa berat, penyakit menular lainnya yang membahayakan jiwanya, kehamilan, atau terganggu dan hilangnya fungsi reproduksi korban. Bentuk hukumannya adalah pidana penjara paling singkat 4 tahun dan paling lama 20 tahun disertai pidana denda paling sedikit Rp. 160.000.000,00 dan paling banyak Rp. 800.000.000,00. Sedangkan dalam fiqh jinÃ¢yah, penambahan 1/3 hukuman termasuk dalam teori al-âuqÃ»bah al-badaliyyah al-takmÃ®liyyah (hukuman pengganti dan pelengkap). Pemidanaan al-âuqÃ»bah al-badaliyyah al-takmÃ®liyyah merupakan hukuman tambahan yang mengikuti hukuman pokok setelah dikeluarkannya putusan dari hakim. Hukuman yang termasuk dalam jarÃ®mah ini adalah hukuman badan ditambah hukuman diyah kÃ¢milah.Kata Kunci: Penambahan, hukuman, perdagangan orang, hukum pidana Islam.